Stature estimation from anthropometric measurements of footprints in Lun Bawang, an indigenous ethnic group of east Malaysia by linear regression analysis - T. Nataraja Moorthy,; Hairunnisa Mohd Anas Khan, (Malaysian Society of Applied Biology, 2016)
The footprint is a valuable physical evidence encountered in the crime scenes and examination of barefoot impressions is important especially in developing countries like India, Malaysia where the majority of the rural population like to walk barefooted. Most of the foot/foot print studies were conducted on mixed population. But racial and cultural aspects of foot morphology must be considered while conducting such studies. Hence the present study aims to estimate stature from bilateral footprints collected from 230 (115 males, 115 females) consenting adult Lun Bawang ethnics, indigenous groups residing in Sarawak state, east Malaysia. The height of the individuals and footprints were collected following the standard procedure. The data obtained were analyzed with PASW 20 computer software and derived regression formulae to estimate stature from footprint lengths of Lun Bawang ethnics. The investigation revealed that all footprint lengths exhibit statistically positive significant correlation with stature (p<0.001). Correlation coefficient (R) values are found to be higher in the pooled sample (0.862–0.883) when compared with males (0.718–0.760) and females (0.754–0.802). The regression formulae derived for the pooled sample can be used to estimate stature when the sex of the footprint remains unknown, as in real crime scenarios.